Problem: Let $ (X_1,X_2, \ldots, X_n) $ be a random sample from Pareto Distribution with pdf

$ f(x; \theta) = (\frac{\theta}{c})(\frac{c}{x})^{\theta + 1}, ~~ x> c $. Find the UMVUE of parameter $ \theta$.

My work so far: I proved that the UMVUE cannot be found through Cramer-Rao method. Then

I tried with the classic Rao Blackwell method: I proved that the given Pareto Distribution is

included in the Exponential Family and $T = \sum_{i=1}^{n} \log X_i $ is a complete and sufficient statistic

of $ \theta $. Now I am stuck because I could not find an unbiased estimator of $ \theta $ to proceed.

  • 2
    $\begingroup$ You might want to consider whether you can say that if you know $c$ then $\sum_{i=1}^{n} \log X_i - n\log c$ has a Gamma (or Erlang) distribution with rate $\theta$ and mean $\dfrac{n}{\theta}$ $\endgroup$ – Henry Nov 22 '16 at 19:17
  • $\begingroup$ @Henry From that we can conclude that $ \sum_{i=1}^{n} \frac{\log X_i}{n} - \log c $ is the UMVUE of$ \frac{1}{\theta}$, but I cannot see how we can find the UMVUE of $ \theta$. Could you please elaborate further? $\endgroup$ – Greg Nov 22 '16 at 19:29
  • $\begingroup$ That $c$ is known should be added to the question. $\endgroup$ – StubbornAtom Dec 2 '19 at 14:27

We have the joint pdf $$ f(\vec x ; \theta) = \theta^n c^{\theta n} \prod_{i=1}^n x_i^{-(\theta+1)}\mathbb{1}_{x_i \ge c} =\mathbb{1}_{x_{(1)} \ge c} \left[ \theta^n c^{\theta n} \right] \exp \left[ -(\theta+1) \sum_{i=1}^n \ln x_i\right] $$ and so by the Exponential-Family factorization $\sum_{i=1}^n \ln X_i$ is complete & sufficient for the distribution.

For a preliminary result, consider $Y = \ln(X) - \ln(c)$ where $X$ follows from the given pareto distribution i.e. $f_X(x) = \theta c^\theta x^{-(\theta+1)} \mathbb{1}_{x \ge c}$. Then, since $X = ce^Y$, we get $$ f_Y(y) = f_X(ce^Y) \left\vert \frac{dx}{dy} \right\vert = \theta c^\theta (c e^Y)^{-(\theta+1)} \mathbb{1}_{ ce^Y \ge c} \cdot ce^Y = \theta e^{-y \theta} \mathbb{1}_{ y \ge 0} $$ which is the pdf of an exponential rate = $\theta$ distribution. Define $Y_i := \ln(X_i) - \ln(c)$

It follows that $\sum_{i=1}^n Y_i = \sum_{i=1}^n (\ln X_i - \ln (c))$ follows a $\Gamma(n,\theta)$ distribution since it's the sum of $n$ independent exponential rate $\theta$ random variables. Note that the mean of an exponential rate $\theta$ r.v. is $1/\theta$ and the mean of a $\Gamma(n,\theta)$ r.v. is $n/\theta$.

So $\frac{1}{n} \sum_{i=1}^n Y_i$ is an unbiased estimator of $1/\theta$, and it's natural to guess that $1/ \left( \frac{1}{n} \sum_{i=1}^n Y_i \right)$ is an unbiased estimator of $\theta$.

Let $Z \sim \Gamma(n,\theta)$. Then, the expecation of $1/ \left( \frac{1}{n} \sum_{i=1}^n Y_i \right)$ equals: \begin{align*} E \left[ \frac{n}{Z} \right] &= n \int_0^\infty \frac{1}{z} \frac{1}{\Gamma(n)} \theta^n z^{n-1} e^{- \theta z} \; dz \\ &= n \int_0^\infty \frac{1}{\Gamma(n)} \theta^n z^{n-2} e^{- \theta z} \; dz \\ &= n \frac{ \theta \Gamma(n-1)}{\Gamma(n)} \int_0^\infty \frac{1}{\Gamma(n-1)} \theta^{n-1} z^{n-2} e^{- \theta z} \; dz \end{align*} and this equals $\theta n \dfrac{ (n-2)!}{(n-1)!}= \frac{n}{n-1} \theta$ since the rightmost integral is integrating the pdf of a $\Gamma(n-1,\theta)$ random variable over its support.

It follows from Lehmann Scheffe that $\dfrac{n-1}{n} \cdot \dfrac{1}{\frac{1}{n} \sum_{i=1}^n Y_i} = \dfrac{n-1}{\sum_{i=1}^n (\ln X_i - \ln c) }$ is the UMVUE of $\theta$.

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.